Setup and its effect on safety margin in conformal radiotherapy of the prostate - Kragelj, Borut (Radiology and oncology (Ljubljana), 2005)
Background. In radiotherapy, setup errors in positioning the patients influence the size of safety margin and thereby also the size of irradiation field and toxicity of radiotherapy. Methods. The setup errors were calculated by evaluating the deviations from the measured distance between the irradiation field margin and the bony pelvis. Results. The research was performed on 23 patients. With respect to lateral, craniocaudal and anteroposterior axis, the observed systemic error ranged from -5 to + 9 mm, -4to +5 mm, and from -4 to +4 mm, respectively, whereas the observed random error ranged from 0 to 7.5 mm, 0 to 3.6 mm, and from 0 to 4.2 mm, respectively. The safety margin, with the 90% probability to cover clinical target volume (CTV) and allowing for the prostate position variability, measured 9 mm, 9.5 mm, 7 mm, and 10 mm in the respective lateral, craniocaudal, anterior and dorsal direction. Conclusions. Irradiation of the prostate with a 7 mm dorsal safety margin, allowing for 90% coverage probability of CTV, was feasible in 22/23 patients on condition that the grosssystemic error (>3mm) was eliminated.
Keywords: obsevanje; prostata; Prostata, novotvorbe; prostate; Prostatic Neoplasms; radioterapija; Radioterapija, doziranje; Radioterapija, planiranje z računalnikom; Radiotherapy; Radiotherapy Dosage; Radiotherapy Planning, Computer-Assisted; rak (medicina); therapy; zdravljenje